1993
DOI: 10.1093/oxfordjournals.humrep.a138101
|View full text |Cite
|
Sign up to set email alerts
|

IVF treatment of moderate male factor infertility: a comparison of mini-Percoll, partial zona dissection and sub-zonal sperm insertion techniques

Abstract: In this study we examined various techniques of in-vitro fertilization (TVF) for treating couples in whom the male had subnormal semen parameters. We compared two sperm preparation methods (mini-Percoll and conventional swimup) for efficiency of recovery after preparation and for fertilization rates after IVF, and compared the suitability of partial zona dissection (PZD) and sub-zonal sperm insertion (SUZI) to patients with different types of male factor infertility. The mini-Percoll technique allowed the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As this radiation is strongly absorbed by water, the delivery of the 2.94-pm radiation could not be performed through a microscope objective and was only possible through an optical fiber brought in immediate contact with the ZP [20]. The first human pregnancies obtained after ZP drilling with this technique have been reported [18,211. Recently, the intracytoplasmic sperm injection (ICSI) using micropipettes has been proposed as an alternative and promising tool in respect to partial zona dissection (PZD) [221 and subzonal insemination (SUZI) [23]. Future safety assessment of these techniques is needed to fully appreciate the advantageddisadvantages of these approaches.…”
Section: Introduction Words: Assisted Fertilization Infrared Laser mentioning
confidence: 99%
“…As this radiation is strongly absorbed by water, the delivery of the 2.94-pm radiation could not be performed through a microscope objective and was only possible through an optical fiber brought in immediate contact with the ZP [20]. The first human pregnancies obtained after ZP drilling with this technique have been reported [18,211. Recently, the intracytoplasmic sperm injection (ICSI) using micropipettes has been proposed as an alternative and promising tool in respect to partial zona dissection (PZD) [221 and subzonal insemination (SUZI) [23]. Future safety assessment of these techniques is needed to fully appreciate the advantageddisadvantages of these approaches.…”
Section: Introduction Words: Assisted Fertilization Infrared Laser mentioning
confidence: 99%
“…However, the results were inconsistent, and overall fertilization rates were low in patients without prior IVF cycles. PZD resulted in a rate of polyspermy of up to 57%, as the number of sperm entering the perivitelline space could not be controlled (105,106).…”
Section: Figurementioning
confidence: 99%
“…This enabled the treatment of severe male factor infertility, as well as decreased rates of polyspermy due to control over the number of spermatozoa injected (108). It has been demonstrated that up to four spermatozoa could be injected without increasing the rate of polyspermy, while injection of 5-10 sperm was associated with a 50% rate of polyspermy (106). Initial studies reported fertilization rates of 25%-71% with this technique (107).…”
Section: Figurementioning
confidence: 99%
“…The mini‐ (Ord, Patrizio, Marello, Balmaceda, & Asch, ) and continuous‐density centrifugation (Shalika, Dugan, Pelesh, & Padilla, ) methods were originally proposed for poor‐quality sperm samples or samples with a low sperm count. Under those circumstances, the mini‐density gradient (Ng, Liu, & Baker, ; Sakkas et al., ) and single‐layer centrifugation (Abraham, Johannisson, & Morrell, ; Gloria et al., ; Shalika et al., ) procedures recovered significantly more motile, morphologically normal, hypoosmotic swelling test‐resistant spermatozoa in comparison with other sperm separation methods. Therefore, the result of the aforementioned procedures allowed more oocytes to be fertilized per frozen‐thawed straw of semen.…”
Section: Introductionmentioning
confidence: 99%